SOSIALISASI PENERAPAN SANITASI TOTAL BERBASIS MASYARAKAT (STBM) UNTUK PILAR CUCI TANGAN PAKAI SABUN MELALUI PEMBUATAN FASILITAS CUCI TANGAN DI DESA BOLA - Elisabeth Dua Rika; Anyela Aprianti (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2023)
Community-Based Total Sanitation (STBM), includes 5 pillars, namely: stopping open defecation, washing hands with soap, managing drinking water, and household food, securing household waste, and securing household liquid waste. One of the pillars that have not been widely studied was the habit of washing hands with soap and running water in the people of Bola Village. The behavior of washing hands with soap is a behavior to prevent the disease from entering our bodies. In the Thematic Real Work Lecture (KKNT) method, we have held deliberations with the Dusun Bola community to carry out these activities. The activities we carry out are offline-based, namely by making leaflets, providing hand washing facilities, and socializing on how to wash hands properly and correctly. the behavior of washing hands properly and correctly can prevent various diseases.